High Potassium Application Rate Increased Grain Yield of Shading-Stressed Winter Wheat by Improving Photosynthesis and Photosynthate Translocation - Wang, Yi; Zhang, Zhongkui; Liang, Yuanyuan; Han, Yulong; Han, Yanlai; Tan, Jinfang (Frontiers in Plant Science, 2020)
Wheat (Triticum aestivum L) production in Huang-Huai Plain of China has been substantially affected in the past 50 years as a result of the decreasing total solar radiation and sunshine hours. Five potassium application rate (K), 0 (K0), 50 (K50), 100 (K100), 150 (K150) and 250 (K250) mg K2O kg-1 soil, combined with two shading levels, no shading (NS) and shading at early filling stage for 10 days (SE), were randomly designed and conducted by pot culture experiment to investigate the effects of K application on winter wheat growth under SE condition. The results showed that under NS condition, the parameters related to chlorophyll fluorescence characteristics, dry matter productivity and grain yields reached the maximum values at a middle K application rate (100 mg K2O kg-1 soil). The variance analysis showed that the interaction effect of K × S on all test traits reached a significant level (P < 0.05 or 0.01). Higher K application rate (150 and 250 mg K2O kg-1 soil) was advantageous to partially alleviate the damage on the winter wheat photosynthetic system caused by shading stress, to improve photosynthesis and increase fructan content and dry matter translocation percentage , leading to the improvement of the grain yield of SE winter wheat. Therefore, an increase in K application rate was beneficial in terms of achieving a higher grain yield of winter wheat under shading stress.